Die effektiven Konsuln Österreich (-Ungarns) v. 1825-1918 Ihre Ausbildung, Arbeitsverhältnisse und Biografien - Deusch, Engelbert (2017)
I report about education and duties of Austrian consuls from 1825-1918 and their biographies.